ANALISIS PERBEDAAN ABNORMAL RETURN DAN VOLUME ERDAGANGAN SAHAM SEBELUM DAN SESUDAH JANUARY EFFECT PADA SAHAM INDEKS LQ 45 DI BURSA EFEK INDONESIA - Subhan, Muhammad; Hasan, Amir; Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2016)
January is the month of the commencement of trading in every year, in this monthinvestors expect to get high returns from the previous year. In January the stock price islikely to increase from the previous month. This phenomenon by investors and capitalmarket analysts are called the January effect. Anomalies January effect can be used byinvestors in making decisions to buy, sell or retain stocks held.Factors that influence theJanuary effect are the selling pressure made by investors at the end of the year to reducetaxes (tax lost selling) and a Window Dressing, this is namely the selling of the stocks thathave performed poorly in the end year conducted by financial managers with the aim toreport the stock portfolio performance reporting at the end of the year will be look good atthe performance. Besides both cases increasing macro economic growth and optimism ofinvestors on government policies also affect the stock price increases earlier in theyear.This study examined differences Abnormal Return and Trading Volume Activitybefore and after the January Effect in LQ 45 stocks in the Indonesia Stock Exchangeperiod 2013 to 2015. This study uses event study analysis model. The method used is theWilcoxon test, a method to determine the difference in abnormal return and trading volumeof the stock before and after the January effect.Results of analysis Wilcoxon test with levelof significance (Î±), a 5% showed that the difference was significant abnormal returns in2013 and 2014, while the views of the Trading VolumeActivity significant differenceoccurred from 2013 to 2015.